STUDI PEMAHAMAN GOOD GOVERNANCE PADA LINGKUNGAN DPRD KABUPATEN LIMA PULUH KOTA DALAM RANGKA PENGAWASAN PEMBENTUKAN PERATURAN DAERAH - Beni Murdani; Dasep Suryanto (Pusat Riset dan Inovasi Nasional, 2022)
This research is to find out how the understanding of good governance in the DPRD of Fifty Cities Regency is in the context of Supervision of the formation of Regional Regulations. This study used a purposive sampling technique where the researcher selected 9 key informants from different fields and then this research was analyzed by quantitative descriptive. The results of the study show that good governance is basically a concept that refers to the process of achieving decisions and their implementation that can be accounted for together. The importance of understanding good governance is something that must be fulfilled by every member of the DPRD so that the optimization of the supervisory function can run effectively and efficiently. Unproductive in formulating regional regulations, it is necessary to have optimal monitoring and in-depth evaluation of the outputs of regional regulations which will be a reflection of the government in being responsible for the results of these regional regulations. For this reason, it is necessary to have the participation of all stakeholders, including the community.